Fabric Tensors in Bone Mechanics - S. Jemioło; J.J. Telega (Engineering Transactions, 2015)
Mechanical properties of cancellous and cortical bone have been investigated. The fabric tensors used in the relevant literature have been discussed. Nonlinear elastic and elastic-perfectly plastic constitutive relationships have been proposed within the framework of small deformations. To this end the theory of representation of tensor functions has been used. It has been shown that the fabric tensor plays the role of a parametric tensor. Orthotropic linear elasticity has been carefully examined from the point of view of interrelations of classical material constants with the proposed material parameters and eigenvalues of the fabric tensor. Hoffman's strength criterion has been extended by incorporating the fabric tensor. Anisotropic properties of human cancellous and cortical bones have been investigated by using the relations derived.